An Enhanced Ubiquitous-Joint Model for a Rock Mass With Conjugate Joints and Its Application on Excavation Simulation of Large Underground Caverns - Leng, Xianlun; Wang, Chuan; Sheng, Qian; Chen, Jian; Li, Hailun (Frontiers in Earth Science, 2021)
A conjugate jointed rock mass (CJRM) is a rock mass with two sets of intersecting joints formed from intact rock under shear. Its mechanical properties and excavation-induced hazards of large underground caverns are different from those of common rock masses because of the unique geological origin thereof. To demonstrate numerically the excavation responses of CJRM, the ubiquitous-joint model is enhanced by consideration of the specific mechanical behaviors of the rock mass. In the enhanced model, CJRM is considered as the composite of columns of rock and two sets of weak planes of joints. The local coordinates, failure modes, and failure sequences of the rock columns and joints are redefined based on the composite characteristics of CJRM, and the failure criteria and plastic potential functions are accordingly modified. The enhanced model is verified numerically by triaxial compression tests and then employed to simulate the excavation of large underground caverns of a pumped storage power station in China. Results show that the modification of the local coordinate system, failure modes, and failure sequences made in the enhanced model is suited to the simulation of the mechanical behaviors of CJRM. Compared with the original ubiquitous-joint model, the enhanced model allows better predictions of the distribution of plastic zones and magnitudes of deformations in simulating underground excavations in CJRM and helps to assess the excavation-triggered hazards more accurately.